2012
DOI: 10.1016/j.jneumeth.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Repeated assessment of orthotopic glioma pO2 by multi-site EPR oximetry: A technique with the potential to guide therapeutic optimization by repeated measurements of oxygen

Abstract: Tumor hypoxia plays a vital role in therapeutic resistance. Consequently, measurements of tumor pO2 could be used to optimize the outcome of oxygen-dependent therapies, such as, chemoradiation. However, the potential optimizations are restricted by the lack of methods to repeatedly and quantitatively assess tumor pO2 during therapies, particularly in gliomas. We describe the procedures for repeated measurements of orthotopic glioma pO2 by multi-site electron paramagnetic resonance (EPR) oximetry. This oximetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…We furthermore showed a substantial difference between StO 2 estimates in the 9 L glioma model where mqBOLD indicates normal or higher StO 2 in the tumor, while MRvF indicates lower oxygenation. Previous studies using Electron Paramagnetic Resonance (EPR) have reported normal tissue oxygenation in the 9 L model2728. However, other studies using oxygen microelectrodes have reported very low pO 2 measurements (hypoxic) in the 9 L tumors29.…”
Section: Discussionmentioning
confidence: 99%
“…We furthermore showed a substantial difference between StO 2 estimates in the 9 L glioma model where mqBOLD indicates normal or higher StO 2 in the tumor, while MRvF indicates lower oxygenation. Previous studies using Electron Paramagnetic Resonance (EPR) have reported normal tissue oxygenation in the 9 L model2728. However, other studies using oxygen microelectrodes have reported very low pO 2 measurements (hypoxic) in the 9 L tumors29.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore proven difficult thus far to define the optimal fractionation scheme. This change in oxygenation could potentially be monitored by measuring the partial pressure of oxygen in the glioma and adjusting the duration of the on/off sequences [24].…”
Section: Discussionmentioning
confidence: 99%
“…The method requires an injection of an exogenous probe bearing an unpaired electron that is selective in its interaction with oxygen (97). Recently, implantable and metabolically inert paramagnetic lithium phthalocyanine crystals have been utilized as oxygen-sensitive electron paramagnetic resonance (EPR) probes to monitor changes in tissue hypoxia (140). The width of the spectral band corresponding to the probe signal correlates with oxygen concentration.…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiamentioning
confidence: 99%